Global Economic Integration and Its Implications for Developing Countries - Nabila Arum Cahyati (Mustard Journal De Ecobusin, 2024)
This paper explores the post-conflict recovery dynamics in Papua, Indonesia, and focuses on how business opportunities relate to economic reconstruction. Papua has had a long history of conflict that limited its development, and recovery is an essential step towards recovery and inclusive development. Purposive sampling was used to select participants with direct recovery experience. Data were collected using a structured questionnaire, which had closed and open-ended questions, pilot-tested, and content validated to ensure reliability. Paired- samples t-tests, regression, ANCOVA, and Pearson correlation were utilized in quantitative analysis, and qualitative responses were thematically explored. The findings revealed that participants viewed economic reconstruction more favourably (M = 4.10, SD = 0.72) compared with business opportunities (M = 3.75, SD = 0.85). A paired-samples t-test showed that business opportunity perceptions improved significantly after specific interventions (t = 3.25, p < 0.01). Regression revealed reconstruction, infrastructure, government support and community engagement to be the most important predictors, with 70% of variance explained. ANCOVA revealed no significant difference in age group, whereas correlation analysis revealed strong positive relationships between reconstruction and business opportunities. Generally, the results emphasize their mutual dependence and the role of inclusive approaches, long-term governmental support, and community involvement to ensure sustainable recovery.